2000
DOI: 10.1002/1096-9918(200008)30:1<140::aid-sia820>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

XPS study of the adsorption of NH3 on nickel oxide on Ni(111)

Abstract: The aim of the present work was to investigate the initial stages of NH 3 interaction with nickel oxide layers formed on well-defined Ni(111) surfaces. The selected technique was x-ray photoelectron spectroscopy. Ammonia adsorption was performed at 10 −7 mbar and room temperature in a preparation chamber attached to the analysis chamber. After each adsorption, the N 1s core level was analysed and its intensity was plotted as a function of exposure (at the same pressure) to obtain the adsorption kinetics. The X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
6
16
0
Order By: Relevance
“…26, 27 The lower intensity of the 2p satellite peaks and the asymmetrical shape of 2p3/2 indicate the mixed chemical environment of the Ni 2+ ions, which is present in both the octahedral and tetrahedral sites of the spinel lattice. At lower energy, the shoulder of the 2p 3/2 peak can be observed at 852.8 eV 28. This indicates the presence of traces of elemental nickel on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…26, 27 The lower intensity of the 2p satellite peaks and the asymmetrical shape of 2p3/2 indicate the mixed chemical environment of the Ni 2+ ions, which is present in both the octahedral and tetrahedral sites of the spinel lattice. At lower energy, the shoulder of the 2p 3/2 peak can be observed at 852.8 eV 28. This indicates the presence of traces of elemental nickel on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…These B-O based species were detected in B1s and O1s levels together with Na 1s signal from XPS on the used catalyst after cycle 4 (Table 3) and by SEM images as a film (Fig 8.b). After diluted acid washing, the catalytic activity was recovered (cycle 5) despite the XPS characteristic signals of B-O species were still present in the catalyst (191.9 eV, Table 3 bonds assigned according to Ref [18] and [37]) and SEM micrographs (Fig 8.c) show partial recovery of the structural features of A c c e p t e d M a n u s c r i p t the fresh catalyst (Fig 8.a). Quantification of the XPS spectra permitted to calculate B/Co ratio before and after acid washing.…”
Section: Sodium Borohydride Hydrolysismentioning
confidence: 99%
“…Under these conditions, different authors reported epitaxial NiO films. The electronic structure [8,10,[14][15][16][18][19][20] as well as the crystal structure [7,12,17] were investigated. More recently, NiO ultra-thin films grown by molecular beam epitaxy (MBE) at room temperature [8,18] have also been characterized.…”
Section: Introductionmentioning
confidence: 99%